Functional analysis of lysB gene from the lysis module of mycobacteriophage Ms6 - Gil, Ana Filipa Morais Esteves, 1978- (2012)
Tese de doutoramento, Farmácia (Microbiologia), Universidade de Lisboa, Faculdade de Farmácia, 2012